ENVIRONMENTAL LITERATION PROFILE BASED ON GENDER OF STUDENTS OF SENIOR HIGH SCHOOLS IN PEMALANG DISTRICT - Ririn Santoso; Kukuh Sugandi; Indah Sukmawati; Ratnawati Ratnawati; Edi Haryanto; Imam Khazali (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2020)
Environmental literacy is defined as knowledge of the mechanism of action of the natural environment, then the role of humans in it to preserve a sustainable environment. Relations between gender and environmental literacy be interesting to study it is interesting to study the framework of the influence of gender differences on environmental literacy education. This aims of research is to describe the profile of environmental literacy based on gender in high school students in Pemalang Regency. The research subject was students of class XI of SMAN throughout Pemalang District with a total sample of 351 students. Data were collected using a test and questionnaire method. From the results of the research, obtained an average value of environmental literacy profiles for male students at 63.54 and for female students at 64.05. Based on the Sig.Levene's Test for Equality of Variances test of 0.897, it means that the data variance for the male and female groups is homogeneous. Furthermore, data analysis is based on Sig (2 tailed) values of 0.559> 0.05, meaning H0 is accepted and H1 is rejected. Therefore, based on data analysis, there is no significant difference between the environmental literacy profiles of male and female students. Therefore, there is no need for differences in the implementation of assessments in environmental education, both for male and female students.Keywords: enviromental literacy, gender, profile